PROSES PEMBUATAN THUMB SCREW DENGAN MENGGUNAKAN MESIN CNC BUBUT SERTA PEMBUATAN ULIR SECARA KONVENSIONAL DI PT. AMANAH JAYA PERSADA - abas, Jordy hafiz rizaldi; Rachmat , Asep (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Thumb Screws are multi-purpose fasteners designed to be tightened and loosened by hand. They are primarily used to secure cable panel covers, safety covers, battery compartments, and other parts or components that may need to be removed and reinstalled frequently. The screw system is known and has been used by humans for several centuries. The aim of creating this screw system is basically to find an easy way to combine or connect two components so that this combination becomes a single unit that is useful in accordance with its function. The Thumb Screw manufacturing process uses a CNC lathe and conventional tapping. A CNC lathe is used to make the Thumb Screw using Alumunion copper alloy series 2000 material in the form of a long pipe with a length of 26.50 mm and a diameter of 15.20 mm and a tap is used to make the thread hole. Then measure the material dimensions again as the final finishing stage